Synthesis and Characterization of Rise Husk Nanopores Carbon Through Ultrasonic Irradiation With H3PO4 Activators as Electrochemical Energy Storage Materials - Sitti Rahmah; Muhammad Zakir; L. Musa Ramang (Hasanuddin University, 2017)
The research on synthesis and characterization of carbon nanopores rice husk through ultrasonic irradiation by activators H3PO4 as electrochemical energy storage material has been made. This activated carbon is a basic material in making electrodes which will be developed into electrochemical energy storage material. Nanopores carbon is made from rice husks, which passes through three stages of the process and the development methods of manufacturing of previous activated carbon. Carbonization carried out at a temperature of 350 oC, then add the HF with the aim to remove silica from the carbon in order to increase its surface area, and chemical activation with H3PO4. Furthermore, the modified carbon through ultrasonic irradiation. Characterization of the surface of activated carbon is done through the analysis of XRD and XRF, characterization of functional groups by FTIR, surface area determination by the method of methylene blue, as well as the specific capacitance measurement with CV. The results showed the addition HF can remove carbon silica in rice husks. The element largest of the active carbon with ultrasonic wave irradiation is Ca or oxide CaO by 46,43 %, which has a crystallinity of phase with relatively mesoporous carbon pores. The surface area of activated carbon rice husk with irradiation of ultrasonic waves in optimum condition at a temperature of 30 ° C for 60 minutes which is 184.348426 m2 / g. The value of the specific capacity of the activated carbon energy storage rice husks with and without irradiation of ultrasonic waves each is 1067,75 nF/g and 622,17 nF/gram.